Limited Achievements Obama’s Foreign Policy - Laïdi, Z.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2012)
Through an analysis of the general principles of Obama's foreign policy, LaIdi shows how Obama has charted a realist course in the Middle East, in Europe, in diplomacy, and in war.
Keywords: International relations; Europe—Politics and government; Political science; Democracy; International Relations; European Politics; Political Science; Democracy; Foreign Policy